Pemberdayaan Guru Pos PAUD JUARA Melalui Psikoedukasi Berbasis Teori Ekologi untuk Peningkatan Kesehatan Mental dan Pemenuhan Hak-Hak Anak Usia Dini - Esty Faatinisa; Mae Amelianawati; Saepul Adnan; Zahra Putri Aulia; Desinta Agustina Nindi (Pusat Riset dan Inovasi Nasional, 2025)
Improving teachers' competence in supporting mental health and early childhood rights is a crucial issue in the modern era. This service research aims to improve teacher competence through psychoeducation based on Ecological Theory at the Juara PAUD Post in the city of Bandung. This service program starts from planning that contains problem identification, then implementation. Based on the theory of Ecology, this program is not only given to teachers but also to parents as a microsystem of children. These findings indicate that psychoeducational interventions are effective in providing teachers and parents with a new understanding of the importance of children's mental health and rights, as well as equipping them with practical strategies to apply in the learning environment and parenting implementation. The implication of this study is the importance of integrating aspects of educational psychology into early childhood teacher training programs, encouraging active collaboration between teachers and parents, and making schools part of a supportive ecosystem for children's growth and development.